2013
DOI: 10.3350/cmh.2013.19.2.165
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of entecavir plus carnitine complex (GODEX®) compared to entecavir monotherapy in patient with ALT elevated chronic hepatitis B: randomized, multicenter open-label trials. The GOAL study

Abstract: Background/AimsCarnitine and vitamin complex (Godex®) is widely used in patients with chronic liver disease who show elevated liver enzyme in South Korea. The purpose of this study is to identify the efficacy and safety of carnitine from entecavir combination therapy in Alanine aminotransferase (ALT) elevated Chronic Hepatitis B (CHB) patients.Methods130 treatment-naïve patients with CHB were enrolled from 13 sites. The patients were randomly selected to the entecavir and the complex of entecavir and carnitine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Several reports have revealed that carnitine supplementation has a positive effect on various liver diseases. Carnitine supplementation reportedly improves liver steatosis and fibrosis in patients with NASH and decreases alanine aminotransferase levels in patients infected with hepatitis B virus . In addition, we revealed that carnitine supplementation suppresses hepatitis C virus (HCV) replication and HCV‐induced oxidant stress .…”
Section: Discussionmentioning
confidence: 86%
“…Several reports have revealed that carnitine supplementation has a positive effect on various liver diseases. Carnitine supplementation reportedly improves liver steatosis and fibrosis in patients with NASH and decreases alanine aminotransferase levels in patients infected with hepatitis B virus . In addition, we revealed that carnitine supplementation suppresses hepatitis C virus (HCV) replication and HCV‐induced oxidant stress .…”
Section: Discussionmentioning
confidence: 86%
“…Interestingly, among the NTCP inhibitors identified, indomethacin was also previously shown to reduce hepatitis B e antigen (HBeAg) and HBV-DNA in sera of silent HBV carriers (Bahrami et al, 2005; Kapicioğlu et al, 2000). Also, the known NTCP inhibitor L-carnitine showed higher ALT normalization rate in chronic HBV patients (Jun et al, 2013). In addition, a recent in vitro study showed that ezetimibe blocks hepatitis B virus infection by targeting a post-entry step(s) in the HBV life cycle, although minor effects on binding and uptake of viral particles were also observed (Lucifora et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it has been shown that L-Cn displays immune suppressive properties in Crohn’s disease ( 13 , 14 ). On the contrary, previous studies demonstrated the protective effect of carnitine supplementation on ALT normalization in patients with CHB when combined with entecavir, improvement in sarcopenia and hyperammonemia in patients with liver cirrhosis, and hospital admissions reduction in patients with hepatic encephalopathy ( 15 18 ). However, available findings regarding plasma L-Cn levels in patients with chronic HBV infection remain somewhat contradictory, and the effect of L-Cn on the expression of inhibitory receptors and the production of suppressive cytokines by immune cells have not yet been fully elucidated.…”
Section: Introductionmentioning
confidence: 83%